“Ūkiškasis kalendorius” (Kalendarz gospodarski) Lietuvoje tarp dviejų sukilimų (1831–1863 m.) - Budinaitė, Salomėja (Knygotyra, 1991)
“Economical calendar” which was published in Vilnius from 1831 up to 1863 is a typical example of the calendars’ press. It was the only Polish calendar printed in Lithuania till 1842 and from 1842 the only Russian-Polish one. According this calendar L. Ivinskis began to print Lithuanian calendars. The Vilnius Astronomy Obserwatory owned the monopoly of publishing of the calendar.The article reveals the circumstances under which the publication was printed and distributed. In the article the content, structure, destination and editions of the calendar are analysed. The efforts of astronomer M. Gusev to reform the calendar are also presented in the article.“Economical calendar” is an important source to investigate problems of public education, economic structure and social life. There were printed not only calendar data but also information on agriculture, medicine, astronomy, meteorology in these editions.The material of the calendar is estimated from two points: 1) the educational, informational, communicational importance of the calendar in 1831–1863. 2) the actuality of these editions for a contemporary reader and scientist.